Thirteen Years of Counting Migration in Batumi: Observations and Their Importance for Raptor Conservation in Russia - Olga O. Zaitseva; Bart Hoekstra; Wouter Vansteelant (Пернатые хищники и их охрана)
One of the most important autumn migration bottlenecks for birds of prey in the Western Palearctic is situated in South-Western Georgia, between the east coast of the Black Sea and the range of Lesser Caucasus. Every year from mid-August till October at least 1% of the world’s population of 10 raptor species passes through this corridor.